P‐131: Synthesis and Device Application of a Dibenzothiophene Derivative as Thermally Activated Delayed Fluorescence Material for Green Fluorescence OLED. Issue 1 (June 2015) - Kim, Ji Han; Hwang, Seok Ho; Kim, Oh Young; Lee, Jun Yeob
Abstract : The dibenzothiophene derivative, 2, 8‐bis(9, 9‐dimethylacridin‐10(9H)‐yl)dibenzothiophene 5, 5‐dioxide, as synthesized as a thermally activated delayed fluorescence material for green fluorescence organic light‐emitting diodes. The dibenzothiophene derivative had a donor‐acceptor structure for thermally activated delayed fluorescent emission and high maximum quantum efficiency of 14.3% was achieved in green devices.